A Review on Simultaneous Determination of Anti-Hypertensive Drug Combinations Containing Amlodipine Besylate using Chromatographic Analysis - Kumar Chandran, Sajith (Asian Journal of Pharmaceutical Research and Development, 2022)
The present review aims to investigate some of the recently reported analytical methods available for the assay of antihypertensive drugs in various combinations of pharmaceutical forms. Several simultaneous RP- HPLC methods have been reported for the determination of antihypertensive drugs. The review familiarizes various reported methods for the simultaneous determination of Amlodipine besylate with other antihypertensive drug formulations which are used in combination treatment protocols.